Pengaruh Model Pembelajaran Berbasis Masalah Terhadap Motivasi Belajar Dan Hasil Belajar Pada Mata Pelajaran Geografi Di SMA Tahfidz Darul Ulum Banyuanyar Pamekasan - Andri Kurniawan (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2019)
Problem Based Learning model is a model of learning that leads students on real-world problems that make students actively in the teaching learning process so that it can affect to learning motivation and learning outcomes of students in Geography subject. The purpose of this study is (1) to find out whether there are differences in learning motivation and learning outcomes between the Experimental Group and the Control Group before using the Problem Based Learning Model on the Geography subject . (2) To find out the differences in learning motivation and learning outcomes between Experimental Group and Control Group after using Problem Based Learning Model on the Geography subject. The design in this study used a True Experiment Design or a true experimental design type Pretest-Posttest Control Group Design. Sample was taken randomly, while the method and instrument data collection used questionnaires and documentation, Validity Instruments test used correlation Pearson Product Moment and reliability test used Alpha Cronbach with the help of SPSS for windows version 21 as well as the technical analyst data used independent sample t test with SPSS for Windows version 21. The findings showed that: (1) there was no difference in learning motivation and learning outcomes between experimental group and control group before getting treatment with Problem Based Learning Model on the Geography subject, (2) there was difference in learning motivation and learning outcomes between the experimental group after using the Problem Based Learning Model and the control group that did not get treatment with the problem based learning model in Geography subjects or there is influence of Problem Based Learning Model on Learning Motivation and Learning Outcomes in Geography Subject in Senior High School of Tahfidz Darul Ulum Banyuanyar Pamekasan